Micro and Macro Approaches in Linguistics for Method Development - Umul Khasanah (Yayasan Adra Karima Hubbi, 2024)
Background. Micro and macro approaches in linguistics have long been two methods used separately in language research. The micro approach focuses on the technical structure of the language, such as grammar, phonology, and syntax, while the macro approach examines how language is used in a broader social context. However, the separation of these two approaches often creates a gap in understanding the overall use of language. Purpose. This research aims to develop a method that integrates micro and macro approaches in linguistic studies, especially in Japanese. Method. The research method used was mixed, in which quantitative data was collected through a questionnaire from 52 native Japanese speaking respondents, and qualitative data was obtained through in-depth interviews with 10 participants. This study examines how Japanese speakers use language structures in various social contexts, both formal and informal. Results. The results showed that an understanding of the technical structure of language helps speakers in formal situations, such as in the workplace, while social adaptation is necessary in more relaxed situations, such as social media. The integration between micro and macro approaches provides a more comprehensive understanding of how language is used in everyday life. Conclusion. In conclusion, a method that combines these two approaches is essential to get a more complete picture of the dynamics of language use.